Environmental Design for the Reconstruction of PT X Ex-Mine Land Reclamation, Bombana Regency, Southeast Sulawesi Province - Haslinda, Haslinda; Indrayani, Poppy; Chaerul, Muhammad (ASTONJADRO, 2024)
The study area is located in the IUP of PT X, which covers an area of ± 1,210 ha. Administratively located in Bombana Regency, Southeast Sulawesi Province. Spatial data analysis in mapping the potential success rate of reclamation and environmental design is carried out based on geological criteria and remote sensing so that the impact of risks in the mining industry can be minimized. This study aims to map the potential success rate of post-mining land reclamation and environmental design in the study area based on spatial analysis with the Analytical Hierarchy Process (AHP) method. The geological criteria used in this study are lithological units, seismicity, hydrology (catchment area), vegetation density distribution, and hydrothermal alteration (iron oxide alteration and clay minerals). The data used in this study are the Kolaka sheet regional geologic map, DEM SRTM, Landsat 8 imagery, and company reports (lithology, reclaimed land openings). The data were analyzed to produce evidence maps of lithology, ranginess, catchment area, and vegetation density distribution using the NDVI technique and hydrothermal alteration using the band ratio technique, then spatial analysis was carried out using the AHP method. The result of this research is a map illustrating the potential success rate of reclamation and environmental design in the study area which is divided into 3 classes, namely: high potential area of 407.52 Ha (36.68%), medium potential area of 360.81 Ha (32.48%), and low potential area of 342.54 Ha (30.84%) of the total area. Based on the validation test of the reclaimed land opening area of 28.63 Ha that corresponds to the area with the result of a high potential success rate of about 89% of the total validation land opening area the results of this modeling are statistically acceptable.